Peran Asesmen Dalam Pengintensifan Activity of Daily Living Untuk Efektivitas Kemandirian Children With Double Blind - Nadia, Ahsana; Rismadanti, Diska Putri; Fitriya, Salwa; Sani, Hayin Yusnia; Chantika, Intan Karunia; Habibah, Tsamara; Ummah, Umi Safiul; Harisandi, I GST. Ngurah Putu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to obtain information related to identification and assessment, as well as the Activity of Daily Living (ADL) program applied to visually impaired students at SLB SATHITEN Malang City. This research was conducted using the literature study method and descriptive observation where the results of the study show that the role of assessment in identifying the needs of children with visual impairments is very important to understand the child's condition thoroughly and design appropriate interventions. The assessment also helps to identify the extent to which children can be independent in performing activities of daily living (ADL).